UNIFIED DESCRIPTION OF PHOTO AND ELECTRO PROCESSES ON LIGHT NUCLEI IN COVARIANT APPROACH WITH EXACTLY CONSERVED EM CURRENT - P. E. Kuznietsov (East European Journal of Physics, 2015)
Generalized gauge invariant electro-break up process amplitude is considered. One is a sum of traditional pole series and the regular part. The deposits of regular part of amplitude, and its physical sense, are explored. A transition from virtual to real photon is considered in photon point limit q2 →0 . The general analysis for electo-break up process of component scalar system is given. Precisely conserved nuclear electromagnetic currents at arbitrary q2 are received.